High Levels of Circulating Thrombomodulin in Human Foetuses and Children - Menashi, Suzanne; Aurousseau, Marie-Hélène; Gozin, Danielle; Daffos, Fernand; D’Angelo, Armando; Forestier, François; Boffa, Marie-Claire (Thrombosis and Haemostasis, 1999)
Thrombomodulin (TM) is an endothelial cell surface proteoglycan with anticoagulant functions, also implicated in cell proliferation, cell-cell adhesion and differentiation. In this study we determined circulating plasma TM (pTM) levels in human foetuses at different stages of pregnancy, at birth and in childhood. TM levels increased with gestational age, the median level reaching a peak of approximately 165 ng/ml between the 23rd and 26th week, thereafter decreasing gradually, reaching a value of 108 ng/ml at birth. pTM continues to decrease progressively during childhood, reaching in the 5-15 years group a median of 56 ng/ml which approaches the adult value. The pTM peak was statistically significant and represents a specific foetal phenomenon as it was independent of the corresponding maternal values. As a whole, the pTM pattern during foetal maturation appears totally different from that of protein C, prothrombin and other coagulation activators and inhibitors and thus, TM may play in the foetus another role in addition to its well-known anticoagulant function.